Computational investigation of bounded domain with different orientations using CPCM. (April 2019) - Chavan, Santosh; Gumtapure, Veershetty; Arumuga Perumal, D.
Highlights: Effect of orientations on melting and solidification characteristics. Performance analysis of deep and shallow enclosure. Heat transfer analysis of three different wall heating. Melting fraction, flow characteristics and temperature distribution study. Abstract: The present work deals with the composite phase change material (CPCM) of 98% paraffin wax and 2% copper nanoparticle, filled into the bounded domain. Effects of orientation (45°, 90°, 135° and 180°) with different wall heating conditions (base, left and top wall) are analyzed numerically to understand the flow patterns and interface morphology developed during melting/solidification processes. The melting/solidification mechanism exhibited non-uniform flow patterns and irregular morphology which are dependent on geometrical orientations and different wall heating conditions. The results revealed that the bounded domain with different orientations have significant effect on natural convection current formation. As the orientation changes, the heat transfer rate gets influenced significantly and convection currents amplifies. Top wall heating arrangement of 180° orientation shows competence in achieving better thermal performance.